Empowering Public Opinion through Android Applications for Community Participation and Complaint Management - Isa Mukti Widodo; Sutarman (STMIK Budi Darma, 2023)
Various government institutions endeavored to transition towards a e-government system. This initiative aimed to enhance public services, rendering them transparent, effective, and efficient. It enabled citizens to participate in developing and improving public services in Yogyakarta, regardless of time and place. As part of the broader strategy to transition to a e-government system, one practical approach involved leveraging mobile computing devices, such as Android-based mobile applications. Android-based mobile application was used to capture the public's aspirations, thereby fostering the creation of a public opinion that could serve as a benchmark for relevant authorities. This study used an ethnographic approach to identify the features within social media that facilitated the formation of online public opinion. Furthermore, the application utilized GPS technology to pinpoint the locations associated with each aspiration and complaint. All data was securely stored in the Firebase Database, ensuring accessibility and data integrity. Based on the outcomes of this system, this Android application played a pivotal role in categorizing aspirations and complaints based on multiple factors, including user engagement metrics such as comments, likes, and shares, as well as user interactions and content relevance. Notably, content garnered higher engagement levels was more likely to reach a broader and more diverse audience. This research will produce an application that provides insights into recognizing the diverse preferences and affiliations of the community. By doing so, the system can help local government to make informed decisions that align more closely with the needs and desires of their community, thereby contributing to an enhanced and responsive governance framework